Answer

Verified

381.9k+ views

**Hint:**Problems of this type can be easily solved by using the formulas of Arithmetic Progressions. We use the formula of the summation of the terms of an A.P to get an expression and equate it to $187$where we will get the value of the first term of the A.P. Upon doing that we equate the expression of the 17th term to $-13$ which will give us the value of common difference of the A.P, thus we determine the A.P.

**Complete step by step answer:**

We are given that the sum of first $17$ terms of the A.P is $187$and the ${{17}^{th}}$ term is $-13$ .

We use the formula of summation of A.P as shown below

Sum of $n$ terms of an A.P is $\dfrac{n}{2}\left( a+l \right)$

Here $a$ is the value of first term of the A.P and $l$ is the ${{n}^{th}}$ term of the A.P

We already know that $n=17$ and $l=-13$

Therefore, the expression of the summation becomes $\dfrac{17}{2}\left( a-13 \right)$

We now equate the above expression to the given value of sum i.e., $187$ as shown below

$\dfrac{17}{2}\left( a-13 \right)=187$

$\Rightarrow 17\left( a-13 \right)=187\times 2$

$\Rightarrow 17a-17\times 13=187\times 2$

$\Rightarrow 17a-221=374$

$\Rightarrow 17a=374+221$

$\Rightarrow 17a=595$

$\Rightarrow a=\dfrac{595}{17}$

$\therefore a=35$

Hence, the 1st term of the A.P is $35$

We also know that the formula of the value of ${{n}^{th}}$ term of the A.P is $a+\left( n-1 \right)d$

Here, $d$ is the common difference between two consecutive terms of the A.P

We can equate the above expression to $-13$ by putting $a=35$ and $n=17$ as shown below

$35+\left( 17-1 \right)d=-13$

$\Rightarrow \left( 17-1 \right)d=-13-35$

$\Rightarrow 16d=-48$

$\Rightarrow d=-\dfrac{48}{16}$

$\therefore d=-3$

Hence, the common difference between two consecutive terms of the A.P is $-3$

Therefore, the A.P is \[35,\text{ }32,\text{ }29,\text{ }26,\text{ }23,\text{ }20,\text{ }17,\text{ }14,\text{ }11,\text{ }8,\text{ }5,\text{ }2,\text{ }-1,\text{ }-4,\text{ }-7,\text{ }-10,\text{ }-13\]

**Note:**While developing the expression of summation of the terms of A.P we could have also used the formula for summation $\dfrac{n}{2}\left\{ 2a+\left( n-1 \right)d \right\}$ but the problem is the solution will become lengthier. This happens due to the fact that we have to solve two equations simultaneously to get the two variables $a$ and $d$ rather than simply solving each of the equations one by one to get the solutions.

Recently Updated Pages

How many sigma and pi bonds are present in HCequiv class 11 chemistry CBSE

Why Are Noble Gases NonReactive class 11 chemistry CBSE

Let X and Y be the sets of all positive divisors of class 11 maths CBSE

Let x and y be 2 real numbers which satisfy the equations class 11 maths CBSE

Let x 4log 2sqrt 9k 1 + 7 and y dfrac132log 2sqrt5 class 11 maths CBSE

Let x22ax+b20 and x22bx+a20 be two equations Then the class 11 maths CBSE

Trending doubts

Which are the Top 10 Largest Countries of the World?

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

How many crores make 10 million class 7 maths CBSE

The 3 + 3 times 3 3 + 3 What is the right answer and class 8 maths CBSE

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Difference Between Plant Cell and Animal Cell

Give 10 examples for herbs , shrubs , climbers , creepers

Change the following sentences into negative and interrogative class 10 english CBSE

Write a letter to the principal requesting him to grant class 10 english CBSE